2011
DOI: 10.1002/art.30416
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between oral contraceptive use and functional outcome in women with recent‐onset inflammatory polyarthritis: Results from the Norfolk Arthritis Register

Abstract: Objective. Use of oral contraceptives (OCs) may prevent the development of rheumatoid arthritis, but the influence of OC use on disease outcome is unresolved. The purpose of this study was to examine functional outcome and OC use in women with inflammatory polyarthritis (IP).Methods. The Norfolk Arthritis Register (NOAR) is an inception cohort of patients with recent-onset IP. We studied patient-reported history of OC use in 663 women who were born after 1945 and who had not used OCs during followup. OC use du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…The association of OC use with the reported PROs was almost identical for past and current users, although half of the past users were older than age 50 years and may not have used OCs for several years. The results of a study by Camacho et al concerning functional outcomes are in agreement with our data; Camacho et al also reported an association between OC use prior to symptom onset and HAQ values at baseline and during a 5‐year followup . The findings on RAID, RADAI, and PROFAD scores cannot be compared with data from the literature since, thus far, no data have been reported concerning the influence of OCs on PROs in arthritis, except for functional outcomes.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The association of OC use with the reported PROs was almost identical for past and current users, although half of the past users were older than age 50 years and may not have used OCs for several years. The results of a study by Camacho et al concerning functional outcomes are in agreement with our data; Camacho et al also reported an association between OC use prior to symptom onset and HAQ values at baseline and during a 5‐year followup . The findings on RAID, RADAI, and PROFAD scores cannot be compared with data from the literature since, thus far, no data have been reported concerning the influence of OCs on PROs in arthritis, except for functional outcomes.…”
Section: Introductionsupporting
confidence: 89%
“…A recent meta‐analysis could not confirm an OC‐mediated protective effect . Data from the Norfolk Arthritis Register showed that the use of OCs at symptom onset and even years before was associated with beneficial functional outcomes over 5 years . In contrast, long‐term radiologic and functional outcomes after 12 years were not significantly influenced by the use of OCs in an RA cohort from the Netherlands .…”
Section: Introductionmentioning
confidence: 95%
“…Variances in methods, doses, and types of OC, as well as population differences, have been proposed to explain some of these controversies. It has been suggested that OCs alter the course of RA, instead of acting as a predictor, and are associated with a milder type of disease and less disability [12,13]. In a previous study, we did not find any impact of a history of OC use on the risk of RA [2].…”
Section: Introductionmentioning
confidence: 54%
“…A recent study [12] suggested that OC use is associated with mild RA and demonstrated a reduction of disability, measured by HAQ over time, in former OC users, compared with nonusers. Furthermore, current OC users had lower HAQ scores at baseline and over time than did previous users.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this need, there is a paucity of literature on the safety of contraceptives in rheumatoid arthritis. Recent data from the Norfolk Arthritis Register (NOAR), an inception cohort of patients with recent-onset inflammatory polyarthritis, showed that OC use is associated with a beneficial functional outcome [66]. Another cohort study reported non-significant improvement in measures of disease activity and damage in 54 OC users with rheumatoid arthritis compared to 58 non-users [67].…”
Section: Hormonal Contraceptives and Rheumatoid Arthritismentioning
confidence: 99%